'He shall signify from time to time'. Romeo and Juliet in modern English. (3rd April 2017) - Delabastita, Dirk
ABSTRACT: Building on the growing interest among Translation Studies scholars in 'intralingual translation' and hoping to contribute to it by some data-driven descriptive work, this paper sets out to investigate the specific case of rewritings of Shakespeare in modern English. Examples will be taken from Romeo and Juliet (c. 1595), a play for which more than a dozen such versions have been found. These are born from a perceived need to bridge the comprehension gap between Shakespeare's play and later audiences. The paper will look into the nature of this comprehension gap and the various (other) ways of dealing with it, before comparing the corpus of modernized versions of Romeo and Juliet . A great variety of translational approaches emerges from the study, and there is no less variety as to how these rewritings appear to be labelled or classified, suggesting that they belong in a generic no-man's land. The idea of translating Shakespeare into modern English generally invites negative reactions; the main arguments used in these controversies and their underlying political and cultural assumptions are also briefly examined.